Movies Impact on Culture Understanding Through Instagram - Norita Prasetya Wardhani (National Conference on Language, Education, and Technology Proceeding, 2023)
Most higher education students use social media, especially Instagram, in their social lives, and they like watching movies in their leisure time. The lecturer takes advantage of these two things, playing social media and watching movies, to teach English. The lecturer asked the students to watch movies and analyze Western cultures from the movies. This study aimed to know how the students analyzed the movie and how they got to know Western cultures from the movie. This study used a descriptive qualitative research design. Class observation, students' captions in their Instagram posts, and questionnaires were used in this study. The result showed that most of the students could not analyze the culture in the movie because they focused on the subtitles, so they did not pay attention too much to the cultures. They thought that everything that occurred in the movie was something that usually happened. Keywords: Instagram; movie; Western cultures